Efektivitas Terapi Akupunktur pada Pasien Osteoarthritis Lutut : Literature Review - Tarigan, Gladys Ametha; Ahmad Fauzi; Anisa Nuraisa Jausal (Jurnal Anestesi, 2025)
Knee osteoarthritis is a degenerative disease that causes stiffness, pain, and joint deformity, potentially impacting patients' quality of life. Acupuncture is a non-pharmacological therapy option. This study aimed to evaluate the effectiveness of acupuncture therapy in knee osteoarthritis patients using literature searches on PubMed®, Cochrane®, and ScienceDirect® with the keyword "effectiveness therapy of acupuncture for knee osteoarthritis." The analysis showed that acupuncture could reduce pain intensity and improve quality of life through the regulation of inflammatory factor inhibition, neurological activity modulation, stimulation of ?-endorphin release, and antioxidant activation. Further studies are needed to ensure long-term effects and optimize therapy combinations for treating knee osteoarthritis patients.